Dictionary of classical mythology - March, Jennifer R. (Oxford ; Philadelphia : Oxbow Books, 2014)
Jenny March's acclaimed Dictionary of Classical Mythology, first published in 1998 but long out of print, has been extensively revised and expanded including a completely new set of beautiful line-drawing illustrations for this Oxbow edition. It is a comprehensive A - Z guide to Greek and Roman mythology. All major myths, legends and fables are here, including gods and goddesses, heroes and villains, dangerous women, legendary creatures and monsters. Characters such as Achilles and Odysseus have extensive entries, as do epic journeys and heroic quests, like that of Jason and the Argonauts to w.
Cover; Dedication; Title Page; Copyright; Contents; Preface; Introduction; The Dictionary; A; B; C; D; E; F; G; H; I; JK; L; M; N; O; PQ; R; S; T; U-Z; Appendices; Maps; Genealogical Tables; Greek and Latin Authors; Select Bibliography; Illustrations.
Includes bibliographical references.
Online resource; title from digital title page (viewed on September 9, 2014).
Master record variable field(s) change: 072
Keywords: Mythology, Classical -- Dictionaries; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Antiquities & Archaeology; Mythology, Classical; HISTORY / Ancient / Greece; Electronic books; Dictionaries